STorM - A Hypermedia Authoring Model for Interactive Digital Out-of-Home Media - Freesz Jr., Marco A.; Yung, Ludmila; Moreno, Marcelo F. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Among the several vehicles of social communication, digital signage displays have been playing a remarkable role in both public and private spaces. Such Digital Out-of-Home (DOOH) media allows for the rapid dissemination of collective, multimedia information to a large number of people. It is observed, however, that there is a large distance between the graphical abstractions offered by DOOH authoring tools and the underlying language for the representation of hyper/multimedia content. Document representation becomes complex, sometimes makes use of scripting languages, and therefore is illegible by authors and even difficult for automated information extraction. In this context, this paper proposes STorM, a hypermedia model and its language STorML that defines higher-level entities related to the concepts found in the audiovisual industry, such as scenes, tracks and media.